2024
DOI: 10.3390/antiox13040434
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Mitochondrial Potassium Channels Activity

Joanna Lewandowska,
Barbara Kalenik,
Antoni Wrzosek
et al.

Abstract: Redox reactions exert a profound influence on numerous cellular functions with mitochondria playing a central role in orchestrating these processes. This pivotal involvement arises from three primary factors: (1) the synthesis of reactive oxygen species (ROS) by mitochondria, (2) the presence of a substantial array of redox enzymes such as respiratory chain, and (3) the responsiveness of mitochondria to the cellular redox state. Within the inner mitochondrial membrane, a group of potassium channels, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…Additionally, mitochondrial tandem pore domain K + channels TASK-3 interact also with the respiratory chain. A recent report revealed a similar interaction between the mitoKv1.3 channel and respiratory chain complex I (for review see Lewandowska et al, 2024).…”
Section: Mitochondrial Context Of Potassium Channel Regulationmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, mitochondrial tandem pore domain K + channels TASK-3 interact also with the respiratory chain. A recent report revealed a similar interaction between the mitoKv1.3 channel and respiratory chain complex I (for review see Lewandowska et al, 2024).…”
Section: Mitochondrial Context Of Potassium Channel Regulationmentioning
confidence: 95%
“…It is well-known that mitoK channels interact with various mitochondrial proteins, some of which are involved in the respiratory chain. These observations were recently summarized (Lewandowska et al, 2024). For instance, it has been suggested that mitoK ATP channels interact with succinate dehydrogenase.…”
Section: Mitochondrial Context Of Potassium Channel Regulationmentioning
confidence: 99%